Investigation of stress, defect structure and electrical conduction in large diameter III‐nitride epitaxy on silicon substrates. Issue 4 (18th March 2015) - Chung, G.; Loboda, M. J.; Carlson, E.; Ewoldt, D.; Ng, T.; Shepherd, D.
Abstract: The results of studies focused on understanding materials‐electrical correlations for GaN‐based films deposited on 150 mm diameter Si wafers in a batch MOCVD system are reported. A wide range of film stress and electrical conduction is observed at consistent and good X‐ray FWHM values. The vertical leakage currents show a strong asymmetry on the polarity of the bias voltage. Film stress (wafer bow) and impurity variations in the buffer layers show no correlation with leakage currents. Surface pit formation and conductive interfaces are critical to determine the leakage currents in buffer layers. TEM image confirms that surface pit stems from voids in Si substrate. The vertical leakage currents follow the Frenkel‐Poole conduction model at the trap energy of 0.7 eV. Vertical leakage currents measured in films can be reduced by a novel, post‐growth process. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)